Mapping Flows of Thought in Islamic Education: Implications for Educational Practice - Isman Ahadi Lebu Raya; Muhtadi Abdul Mun’in (Penerbit Hellow Pustaka, 2024)
This research discusses the phenomenon of Islamic education which is expressed in various types and forms that have long developed among society. Just as the social environment has a strong philosophical foundation. The flow contained in philosophy is now starting to be put forward as a pattern of thinking about something to study it in depth or detail until finding the truth. In fact, philosophy is learning that has a correlation with the nature of truth and the existence of something and is related to someone's right/bad behavior. With the existence of philosophical schools in Islamic education, this can have implications for the practice of Islamic education and its development. As each school has its own characteristics, mapping the three schools can facilitate the stages of educational practice, as well as understanding the main implications of this school of Islamic education. With this convenience, it is hoped that each educational stream regarding educational practices can produce or create new innovations related to educational practices in accordance with existing streams. Because of the existence of philosophical schools in Islamic education, it is also able to overcome various problems that exist in the field of education